Antibacterial potential of Ni-doped zinc oxide nanostructure: comparatively more effective against Gram-negative bacteria including multi-drug resistant strains. Issue 3 (8th January 2020) - Naskar, Atanu; Lee, Sohee; Kim, Kwang-sun
Abstract : Synthesis of Ni 2+ -doped ZnO nanoparticles and their antibacterial activity. Abstract : Infections by multidrug-resistant (MDR) bacteria are one of the most threatening concerns for public health. For this purpose, nanomaterials have emerged with great potential for antibacterial activity. In this paper, we report the synthesis of new Ni 2+ -doped zinc oxide (Ni-ZnO or NZO) nanostructures as targeted antibacterial agents for Gram-negative bacteria. A one-pot low-temperature solution process was used with varying compositions containing 2 or 5% Ni 2+ relative to Zn 2+, resulting in 2NZO or 5NZO, respectively. X-ray diffractometry, transmission electron microscopy, and X-ray photoelectron spectroscopy were used for material characterization. Further, the antibacterial activity against both Gram-negative [ Escherichia coli ( E. coli ) and Acinetobacter baumannii ( A. baumannii ) strains including standard, MDR, and clinical isolates associated with mcr-1 gene] and Gram-positive ( Staphylococcus aureus and Staphylococcus epidermidis ) bacteria were evaluated through analysis of zone of inhibition, minimum inhibitory concentration (MIC), and scanning electron microscopy images. Among the prepared nanostructures, the 5NZO sample showed excellent antibacterial activity against MDR strains of A. baumannii and E. coli . In addition, samples of NZO generated approximately 7 to 16 times more reactive oxygen species (ROS) in E. coli compared to ZnO. Our synthesized nanomaterials have the potential to fight MDR and colistin-resistant Gram-negative bacteria.